2020
DOI: 10.1371/journal.pone.0228281
|View full text |Cite
|
Sign up to set email alerts
|

Making consultation meaningful: Insights from a case study of the South African mental health policy consultation process

Abstract: Background It is widely recognised that mental health policies should be developed in consultation with those tasked with their implementation and the users affected by them. In the South African legislative context public participation in policymaking is assumed, with little guidance on how to conduct consultation processes, nor how to use consultation inputs in policy decisions. Methods The South African Mental Health Policy Framework and Strategic Plan was adopted in 2013 after an extensive consultation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 48 publications
(71 reference statements)
1
29
0
Order By: Relevance
“…Africa is a diverse society with a varying culture that elevates masculine norms with a negative perception of mental health challenges that would benefit from policies or models that is concise and clear. However, while taking into account the fact that most Africa countries do not have functional mental health policies and often operate dated ones (Gureje and Alem, 2000;Marais et al, 2020), it is expected that the proposed model in this chapter will take an inclusive standpoint as argued by Hall et al (2020), and can be built on to bolster positive wellbeing among African men. Below is the proposed inclusive model with four levels.…”
Section: Models Of Remedymentioning
confidence: 99%
“…Africa is a diverse society with a varying culture that elevates masculine norms with a negative perception of mental health challenges that would benefit from policies or models that is concise and clear. However, while taking into account the fact that most Africa countries do not have functional mental health policies and often operate dated ones (Gureje and Alem, 2000;Marais et al, 2020), it is expected that the proposed model in this chapter will take an inclusive standpoint as argued by Hall et al (2020), and can be built on to bolster positive wellbeing among African men. Below is the proposed inclusive model with four levels.…”
Section: Models Of Remedymentioning
confidence: 99%
“…Through analysis of key informant interviews, policy documents, and consultation summit transcripts, it addressed the question of how the consultation process enabled or constrained movement of knowledge from enacted to inscribed forms. The findings of this study are detailed in a previous paper [ 21 ]. The analysis showed that no substantive changes were made to the mental health policy document following the consultation summits and suggested that the consultation may have been a rubberstamping exercise, although this was not explicitly communicated to consultation participants [ 21 ].…”
Section: Introductionmentioning
confidence: 96%
“…The findings of this study are detailed in a previous paper [ 21 ]. The analysis showed that no substantive changes were made to the mental health policy document following the consultation summits and suggested that the consultation may have been a rubberstamping exercise, although this was not explicitly communicated to consultation participants [ 21 ].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations